Bioreactor-based mass production of human iPSC-derived macrophages enables immunotherapies against bacterial airway infections - Mania Ackermann (Nature Portfolio, 2018)
Pulmonary infections constitute a substantial health problem worldwide. Here the authors show that phagocytes similar to primitive macrophages can be generated from human induced pluripotent stem cells, by the use of industry-compatible, stirred-tank bioreactors, and applied as a cell-based therapy to treat acute bacterial infections in mice.